Perancangan Dashboard Dalam Meningkatkan Efektivitas Manajemen Penjualan Tiket Pesawat Pada PT JKL - Qadriah, Sekar Aurannisa Ramdhani; Angela, Octarifa; Nurkholiza, Rahmiyana; Arisandi, Desi; Beng, Jap Tji (STMIK Banjarbaru, 2024)
This study aims to design a data-driven dashboard to enhance the effectiveness of airline ticket sales management at PT JKL. The dashboard was developed using the Prototype method and the ETL (Extract, Transform, Load) process to construct a Star Schema, enabling efficient data integration from various sources. Leveraging Power BI, the dashboard provides interactive visualizations of sales data, including the number of flights, revenue, discounts, payment methods, and the most frequently booked airlines. The implementation of this dashboard not only simplifies data analysis but also supports faster and more accurate decision-making. Testing results showed that all dashboard features functioned as specified, with Black Box validation achieving